The Influence of Managerial Ownership, Institutional Ownership, and Capital Structure on Tax Avoidance - Ni Made Cindy Wahyu Ramadhanti; Ni Putu Budiadnyani; I Nyoman Sunarta (Universitas Muhammadiyah Makassar, 2025)
This study examines the effect of managerial ownership, institutional ownership, and capital structure on tax avoidance among manufacturing firms listed on the Indonesia Stock Exchange during the period 2021–2023. The analysis was conducted using a quantitative approach, with data processed through the Structural Equation Modeling (SEM) technique and analyzed using SPSS software. The results show that managerial ownership has a negative but statistically insignificant impact on tax avoidance, indicating that variations in internal managerial shareholding do not meaningfully influence corporate tax behavior. Conversely, institutional ownership exhibits a positive and statistically significant effect, suggesting that increased institutional oversight correlates with higher tax avoidance practices. Furthermore, capital structure is also found to have a positive and significant relationship with tax avoidance, implying that firms with higher debt ratios are more likely to engage in aggressive tax planning. These findings underscore the role of external ownership and financial leverage in shaping corporate tax strategies, while highlighting the limited influence of managerial equity stakes. The study offers important implications for regulators and stakeholders in designing governance and financial policies that promote responsible tax practices within the manufacturing sector in Indonesia.